Determinants of the sustainability of capability-based culinary businesses: evidence from urban areas in Central Java Province - Supramono, Supramono; Mahardhika, Dhoni Rizky Widya; Lestari, Utami Puji (Business, Management and Economics Engineering, 2025)
Purpose – Amidst the increasing public awareness of the need for environmentally friendly products and social concerns, sustainability practices can be utilized as a source of competitive advantage for businesses in the culinary industry. The purpose of this study is to investigate the effects of entrepreneurial marketing, transformation capability, and financial capability on sustainability. Research methodology – This study was based on field survey data involving 315 culinary business actors in the cities of Semarang, Salatiga, and Surakarta, Central Java Province. The data analysis used the Partial Least Squares Structural Equation Modeling (PLS-SEM) method.Findings – The determinants of sustainability predicted through the formulation of nine hypotheses are mostly proven empirically. Entrepreneurial marketing, transformation capability, and financial capability are demonstrated to have a positive effect on all dimensions of sustainability including economic, environmental, and social performance. Research limitations – The objects of this research were limited to culinary business actors in urban areas so that only limited generalizations could be made. Future studies can be directed to involve business actors in rural areas so that they can capture the dynamics of sustainability practices better. Practical implications – A policy that can be proposed based on research findings to the government in order to improve sustainability practices is to improve the capabilities of culinary business actors through training and mentoring that emphasize the importance of creating customer value, renewing company operations, and having financial literacy. Originality/Value – This study fills the research gap by introducing a capability-based sustainability determinant model.